Mapping the molecular chaperone interaction network in yeast - Houry, Walid A. (Henry Stewart Talks, 2012)
Large scale proteomic screening in yeast, The TAP-tag pulldown approach, Understanding the principles governing protein homeostasis, Mapping the network of the Hsp90 chaperone using physical and genetic interaction screens, Unraveling the role of Hsp90 in pre-rRNA processing